The Knight at Dawn : Magic Tree House #2 - Osborne, Mary Pope; Murdocca, Sal (New York : Scholastic, 1993)
Eight-year-old Jack and his younger sister Annie use the magic tree house to travel back to the Middle Ages, where they explore a castle and are helped by a mysterious knight.
Accelerated Reader AR
Reading Counts RC
Keywords: Knights and knighthood -- Fiction; Time travel -- Fiction; Castles -- Fiction; Middle Ages -- Fiction; Magic -- Fiction; Tree houses -- Fiction